The virtual manager : cutting-edge solutions for hiring, managing, motivating, and engaging mobile employees - Sheridan, Kevin, 1960- (Pompton Plains, NJ : Career Press, 2012)
'The mere suggestion of employees working from home is enough to make many managers sweat. Faced with the prospect of managing an employee they can't even see, many discover that their managerial style just doesn't work anymore. As an increasing number of jobs can be executed from home, managers must learn how to adapt their leadership style to cater to remote employees. Based on years of research, The Virtual Manager provides any manager with the tools he or she needs to successfully work with virtual employees. Trust us: it's not like managing office-bound employees! This book is a tell-all user manual for a new generation of managers. To stay competitive in a global marketplace, it is essential to incorporate virtual employees into talent management strategy. The Virtual Manager arms managers with the knowledge they need to be become effective virtual leaders, including actionable advice on how to: Leverage the top engagement drivers for virtual employees; Develop or alter policies and procedures to fit virtual employees' needs; Impact business outcomes through a flexible work strategy'--
Includes bibliographical references and index.
Keywords: Telecommuting -- Management; Virtual work teams -- Management; Employee motivation; Organizational effectiveness